Students’ Perception on the Language Used by the Lecturers in Teaching English at the Eight Semester Students of English Department of FKIP UKI Toraja - Nilma Taula'bi' (Publikasi dan UKI Press UKI Toraja., 2019)
The objective of the research was to know the students’ perception on the language used by the lecturers in teaching at the eight semester students of English Department of FKIP UKI Toraja. In this research, the writer used qualitative method. The participant is the eight semester students of English Department of FKIP UKI Toraja academic year 2017/2018. This research employed a snowball sampling where the writer took only 12 students as respondents. Interview was used by the writer in collecting the data. The result showed that the eight semester students of English Department FKIP UKI Toraja is students was really like when lecturers used two language in teaching that is mixing language Indonesian and English